Cross-Reactivity as a Mechanism Linking Infections to Stroke - Lucchese, Guglielmo; Flöel, Agnes; Stahl, Benjamin (Frontiers in Neurology, 2019)
The relevance of infections as risk factor for cerebrovascular disease is being increasingly recognized. Nonetheless, the pathogenic link between the two entities remains poorly understood. Consistent with recent advances in medicine, the present work addresses the hypothesis that infection-induced immune responses may affect human proteins associated with stroke. Applying established procedures in bioinformatics, the pathogen antigens and the human proteins were searched for common sequences using pentapeptides as probes. The data reported demonstrate massive peptide sharing between infectious pathogens—such as Chlamydia pneumoniae, Streptococcus pneumoniae, Tannerella forsythia, Haemophilus influenzae, Influenza A virus and Cytomegalovirus—and human proteins related to risk of ischemic and hemorrhagic stroke. Moreover, these data confirm that the shared peptides are also evident in a number of epitopes experimentally proven immunopositive in the human host. The present data suggest cross-reactivity as a potential mechanistic link between infections and stroke.